Primary and secondary prevention strategies against illicit drug use among adults aged 18–25: a narrative review. (February 2020) - Singh, Shalini; Balhara, Yatan Pal Singh; Gupta, Prashant; Christodoulou, Nikos G
Objectives: We reviewed the literature for preventive programs against illicit drug use that specifically target adults aged 18–25 (i.e. emerging adults). Methods: Narrative review of preventive programs that have a high strength of recommendation according to the US Preventive Services Task Force (USPSTF) grading system. Results: Prevention programs that met the criteria are school and college based, family-based, community based, peer-led, workplace-based, and technology-based interventions. They target the known modifiable risk factors associated with illicit drug use among adolescents and young adults. Conclusion: The preventive programs we reviewed are utilizing evidence-based strategies for the prevention of illicit drug use. Further research is needed to formulate new and effective preventive strategies for the reduction of illicit drug use by emerging adults.